2000
DOI: 10.1577/1548-8667(2000)012<0246:tkoodi>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics of Oxytetracycline Degradation in Deionized Water under Varying Temperature, pH, Light, Substrate, and Organic Matter

Abstract: The kinetics of oxytetracycline (OTC) degradation in deionized water was studied under the influence of various environmental factors. The experiment was conducted with a solution of 10 g aqueous OTC /mL in 600-mL glass beakers under controlled laboratory conditions. The aqueous concentration of OTC was determined by high-performance liquid chromatography. Low temperatures (4ЊC) favored high drug stability, and high temperatures (43ЊC) speeded OTC degradation, resulting in a very short half-life of 0.26 Ϯ 0.11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 20 publications
6
62
2
1
Order By: Relevance
“…2). The rate of decrease was small in comparison with the reports of Doi and Stoskopf (2000) and Kulshrestha et al (2004), who showed that adsorption decreased rapidly over this pH range and reported a strong correlation between pH and the sorption capacity of TC. Adsorption increased slightly at pH 10.…”
Section: Effect Of Ph On Otc Sorption Onto Untreated Montmorillonitecontrasting
confidence: 66%
See 2 more Smart Citations
“…2). The rate of decrease was small in comparison with the reports of Doi and Stoskopf (2000) and Kulshrestha et al (2004), who showed that adsorption decreased rapidly over this pH range and reported a strong correlation between pH and the sorption capacity of TC. Adsorption increased slightly at pH 10.…”
Section: Effect Of Ph On Otc Sorption Onto Untreated Montmorillonitecontrasting
confidence: 66%
“…This can be related to the higher concentration of negative surface charges of clay particles in the alkaline medium. The decrease in efficiency may be related to the possible degradation of the drug in alkaline medium (Doi and Stoskopf 2000). However, similar pH-dependent adsorption trend is absent in low OTC concentrations (0.20, 0.36 mmol L -1 ).…”
Section: Adsorption Isothermsmentioning
confidence: 89%
See 1 more Smart Citation
“…After the period of exposure to OTC, according to Doi and Stoskopf (2000), this antibiotic hardly degrades in water under the conditions of this study.…”
Section: Terramycinmentioning
confidence: 69%
“…Tetracyclines are stable in acid media, but not in alkaline conditions, and form salts in both conditions (Doi, 2000;Halling-Sørensen, 2002). Their water solubility ranges between 230 and 5200 (mg L…”
Section: Persistence Of Different Types Of Antibiotics 331 Tetracycmentioning
confidence: 99%